A critical review of intrinsic and extrinsic antimicrobial properties of insects. (April 2022) - Hadj Saadoun, Jasmine; Sogari, Giovanni; Bernini, Valentina; Camorali, Chiara; Rossi, Flavia; Neviani, Erasmo; Lazzi, Camilla
Abstract: Background: Sustainable nutrition and food security are central topics in the current global agenda. Insect production represents a promising food source that has received growing attention in the food and feed industry due to its high nutritional value and positive effect on animal health. The resilience of insects to infections by different parasites indicates they are an excellent type of biomass for the extraction of various antimicrobial compounds. Scope and approach: The antimicrobial potential of insects is illustrated through a description of the different sources of antimicrobial compounds. Distinctions between intrinsic and extrinsic insect antimicrobials are presented in terms of their constituent components and metabolites produced. An updated overview of potential applications in food and feed sectors is presented to identify key reasons to invest in this food source and to stimulate further research in this field. The main aspects supporting the development of this industry in the future are summarized. Key findings and conclusions: Processing extracted insect fractions will lead to the development of new application possibilities and an increase in the edible insect sector value. The possibility of producing new generation antimicrobials from a sustainable supply chain involving insect rearing contributes to green economy policies and reduction of antibiotic resistance. Highlights: Insects are an excellent biomass to extract different valuable antimicrobials. Insect extracts can increase the economic viability of the insect value chain. Insects can become a primary source of chitin/chitosan. Discovery of new AMPs is a hot topic in the antimicrobial resistance era.